2005
DOI: 10.1111/j.1601-0825.2005.01125.x
|View full text |Cite
|
Sign up to set email alerts
|

Clinicostatistical study of carotid calcification on panoramic radiographs

Abstract: The results show carotid calcifications detected on panoramic radiographs can be used to help predict vascular strokes in patients. In cases where calcified carotid artery atheromas are detected, the dentist or oral and maxillofacial surgeon should refer the patient to a specialized physician.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
36
4
5

Year Published

2010
2010
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(55 citation statements)
references
References 9 publications
6
36
4
5
Order By: Relevance
“…Also, they found that the CACs were not significantly different between the males and females. But Bayram et al (9) and Tamura et al (8) revealed that the incidence of the CAC was higher in female patients. Also, Bayram et al (9) reported that the CAC prevalence was 2.1%.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Also, they found that the CACs were not significantly different between the males and females. But Bayram et al (9) and Tamura et al (8) revealed that the incidence of the CAC was higher in female patients. Also, Bayram et al (9) reported that the CAC prevalence was 2.1%.…”
Section: Discussionmentioning
confidence: 99%
“…In our case, curvilinear homogeneous opacifications were not initially observed on the axial images, but on the axial 3D reconstructed image they were observed. It is reported that CACs were unilateral and located on the left side rather than the right side in normal populations (8). Şişman et al (1) retrospectively investigated the prevalence on 750 PRs in a Turkish population.…”
Section: Discussionmentioning
confidence: 99%
“…They found that the CACs were not significantly different between the males and females. But Tamura et al 17 and Bayram et al 18 revealed that the incidence of the CAC was higher in female patients. Contrary to other studies, 1,17,18 we found that the incidence of the CAC was higher in male patients.…”
Section: Discussionmentioning
confidence: 99%
“…The discrepancy between the frequency of CAC and tonsillolith in our study and that in other studies. 1,10,17,18,27 may be due to the number of patients examined, the patient sample, and the difference in the examining techniques and equipment. This study has some limitations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation